1992
DOI: 10.1128/iai.60.12.5004-5012.1992
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intestinal guanylate cyclase by the heat-stable enterotoxin of Escherichia coli (STa) and protein kinase C

Abstract: The heat-stable enterotoxin of Escherichia coi (STa) stimulates membrane-bound guanylate cyclase in intestinal epithelium and induces fluid and ion secretion. Using the T84 human colon carcinoma cell line as a model, we observed that phorbol esters markedly enhanced STa-stimulated cyclic GMP accumulation in T84

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…In polarized intestinal epithelial cells, activation of GC-C results in the stimulation of cGMP-dependent protein kinases that regulate the opening of CFTR channels and Clsecretion, as well as a inhibition of Na + absorption by interference with a Na/H antiporter. STa was reported to induce an increase in [Ca 2+ ]i, that leads to the activation of the protein kinase C (PKC) required for the stimulation of a membrane-bound guanylyl cyclase (Crane and al., 1992; Fig. 1) .…”
Section: Ca 2+ Regulation Of Nucleotide Cyclasesmentioning
confidence: 99%
“…In polarized intestinal epithelial cells, activation of GC-C results in the stimulation of cGMP-dependent protein kinases that regulate the opening of CFTR channels and Clsecretion, as well as a inhibition of Na + absorption by interference with a Na/H antiporter. STa was reported to induce an increase in [Ca 2+ ]i, that leads to the activation of the protein kinase C (PKC) required for the stimulation of a membrane-bound guanylyl cyclase (Crane and al., 1992; Fig. 1) .…”
Section: Ca 2+ Regulation Of Nucleotide Cyclasesmentioning
confidence: 99%
“…Studies with intestinal epithelial cells in vitro have demonstrated that PKC activation has sequential stimulatory and inhibitory effects on chloride secretion (18,260,341,552). Furthermore, PKC activation may modulate the secretory and biochemical responses to both cyclic AMP-and cyclic GMP-dependent agonists (84,85,268,313,567,572). PKC activation also leads to reversible disassembly of the intestinal epithelial cell cytoskeleton and thus modulates tight junctional function (208).…”
Section: Established Mechanisms Of Intestinal Secretionmentioning
confidence: 99%
“…An unresolved issue to date has been how these data account for receptors of high and low affinity identified in native intestinal tissue and, more recently, human intestinal epithelial cells in vitro (T84) (161,225). Other investigators, however, have identified only low-affinity receptors in T84 cells (85,193,560). A recent study has identified both high-and low-affinity STabinding sites in COS-7 cells expressing GC-C, consistent with expression of different oligomers of the protein by these cells (99).…”
Section: E Coli Heat-stable Enterotoxin a (Sta Sti St P St H )mentioning
confidence: 99%
“…Heat-stable enterotoxin of E. coli [4] and Y. enterocolitica [3] triggers intestinal secretion by stimulating the membrane-bound guanylyl cyclase and thereby elevating the intracellular levels of cyclic guanosine 3P5P monophosphate (cyclic GMP). E. coli heat-stable enterotoxin (STa) has been found to elevate the intracellular levels of calcium ([Ca P ] i ) [5] and the Ca P -dependent protein kinase C appears to regulate the activation of guanylyl cyclase [6]. In the present study, we have demonstrated that similar to E. coli STa, NAG-ST increases the [Ca P ] i besides the activation of membrane-bound guanylyl cyclase in isolated rat enterocytes.…”
Section: Introductionmentioning
confidence: 62%